Neutrophil-lymphocyte ratio predict outcome of upper gastrointestinal bleeding in emergency - Chen, Xinyi; Li, Xinqun; Zhao, Guangju; Xu, Wen (Frontiers in Medicine, 2024)
Background The neutrophil-lymphocyte ratio (NLR) is a simple marker of systemic inflammatory responses. The present study aims to evaluate the prognostic significance of the NLR on admission day in predicting outcomes for patients with upper gastrointestinal bleeding (UGIB), which is a prevalent medical emergency. Methods 726 patients who were admitted to our clinic between January 2019 and December 2022 diagnosed with UGIB, and who underwent necessary examinations, were included in the study. The patients’ Glasgow-Blatchford Score (GBS), Full Rockall Score (FRS), and NLR levels were calculated at the first admission. Outcomes were defined as in-hospital mortality, need for blood transfusion, surgical treatment and endoscopic therapy. Patients were categorized into four groups using NLR quartile levels to compare their clinical characteristics, Glasgow Blatchford Score, Full Rockall Score levels, and prognosis. Secondary, we modified FRS and GBS by adding NLR, respectively. We used area under the receiver operating characteristic curve (AUROC) to assess the accuracy of risk prediction for NLR, NLR-GBS, and NLR-FRS improved models. Results Of 726 patients, 6% died in hospital, 23.9% received endoscopic interventon, 4.8% received surgical treatment, and 46.4% received transfusion therapy. Multifactorial logistic regression showed that a high level of NLR was a risk factor for death in patients with UGIB (p = 0.028). NLR, GBS, FRS, NLR-GBS, and NLR-FRS have sufficient accuracy in predicting inpatient mortality, endoscopic treatment, and transfusion treatment, and the differences are statistically significant (p < 0.05). In the comprehensive prediction of adverse outcomes, NLR-GBS has the highest AUROC, and in predicting inpatient mortality, NLR-FRS has the highest AUROC. Conclusion For UGIB patients, a high NLR was strongly associated with high risk UGIB. Combined testing with the GBS and FRS can achieve good predictive results, which is valuable in guiding the pre-screening and triage of emergency nursing care and clinical treatment to ensure that patients receive rapid and effective treatment and improve the quality of care.